Alat Ukur Literasi Sains Pada Pembelajaran IPA Terintegrasi Lingkungan: Sistematika Literatur Review - Desi Adhari; Santiani; Hadma Yuliani; Muhammad Nasir (Kappa Journal, 2024)
The low level of scientific literacy in Indonesia is an important issue that must be addressed. One of the contributing factors is the lack of reliable and valid scientific literacy measurement tools. This study aims to analyze the dimensions and indicators used in developing scientific literacy measurement tools in science learning. The method used is a systematic literature review by collecting and reviewing 18 related research articles in the last 10 years. The results of the analysis show that most studies refer to the PISA framework which includes dimensions of explaining scientific phenomena, designing and evaluating research, and interpreting data and evidence scientifically. The integration of peatlands as a potential learning environment can be an innovative way to improve students' scientific literacy skills.